Writing classroom corrective feedback preferences of lecturers and students in Universiti Teknologi Mara (UiTM) Dungun Campus, Terengganu / Ismi Safia Adila Ibrahim - Ibrahim, Ismi Safia Adila (2013)
Previous studies have revealed that there are many studies on the effects of various type of teacher feedback on students’ writing skills but little research on the preference of feedback and error correction between language educators and students. Therefore, the aim of this study was to identify lecturers’ and students’ preference for error correction in student writing, their belief on the importance of various writing features, their preference for corrective feedback method and students’ strategies of handling the feedback. The study used questionnaire as its instrument and was conducted in UiTM Dungun with involvement of 281 bachelor students and 15 English language lecturers. The finding showed that both groups of respondents shared similar preferences on error correction, their belief on the importance of various writing features, and their preference for corrective feedback method. Also, it is found that students apply various strategies after receiving lecturers’ corrective feedback. This study has shown that the lecturers in UiTM Dungun are aware of their students’ preference and belief. It is hoped that further studies on these issues can include the effect of preference similarity with students’ language accuracy development in their writing